Endogenous Disasters - Petrosky-Nadeau, Nicolas; Zhang, Lu; Kuehn, Lars-Alexander (American Economic Review, 2018)
Market economies are intrinsically unstable. The standard search model of equilibrium unemployment, once solved accurately with a globally nonlinear algorithm, gives rise endogenously to rare disasters. Intuitively, in the presence of cumulatively large negative shocks, inertial wages remain relatively high, and reduce profits. The marginal costs of hiring run into downward rigidity, which stems from the trading externality of the matching process, and fail to decline relative to profits. Inertial wages and rigid hiring costs combine to stifle job creation flows, depressing the economy into disasters. The disaster dynamics are robust to extensions to home production, capital accumulation, and recursive utility. (JEL E22, E23, E24, E32, J41, J63, N12)